Landscape in motion: post-occupations changes in the housing estates of Minha Casa Minha Vida Program - Orsi, Rafael Alves [UNESP] (Univ Federal Para, 2020)
Released in 2009, the Minha Casa Minha Vida Program has been boosted the Brazilian housing production and changes the cities landscape, mainly in peripheral areas where the housing estates or complex of housing estates have been constructed. The urban landscapes analyses reflect the multiples interests and actors (in different scales) and in these housing estate developments are possible understand the relationship between global and national actors and local characteristics with its daily dynamic production of space. This paper aims analyses the post-occupation changes in housing estates from Minha Casa Minha Vida Program, highlighting the antagonistic and complementary movement between local and global scales in the structuring of landscape. With this purpose, it was selected five housing estates in Araraquara to developing the research. Supported by basic bibliography, landscape observation and fieldwork, it was possible to verify the space deep changes, what show great social demands in the se housing estates, but show dreams and hopes of its habitants as well.
Keywords: Landscape; Urban Spaces.; Housing Estate; Minha Casa Minha Vida Program